Examining the ability of empirical correlations to predict subject specific in vivo extrathoracic aerosol deposition during tidal breathing. Issue 3 (4th March 2017) - Yang, Michael Y.; Ruzycki, Conor; Verschuer, Jordan; Katsifis, Andrew; Eberl, Stefan; Wong, Keith; Golshahi, Laleh; Brannan, John D.; Finlay, Warren H.; Chan, Hak-Kim
ABSTRACT: The accuracy of five extrathoracic deposition equations was examined by comparing model predictions with in vivo deposition measurements of 99m Tc-DTPA radiolabeled 0.9% saline delivered via PARI LC Sprint nebulizers in 19 healthy human subjects. The average extrathoracic deposition fraction measured in vivo was 0.19 ± 0.10 (average ± standard deviation). Comparing to this average value, the extrathoracic deposition fraction predicted by Golshahi et al. equation was the most accurate (0.18 ± 0.08), followed by the model described by the ICRP (0.16 ± 0.03). However, prediction of subject-specific deposition proved more challenging; the Golshahi et al. model performed the best of the examined equations, yet showed only a small positive correlation between measured and predicted deposition in individual subjects with a Pearson correlation coefficient of 0.34. The difficulties in predicting subject-specific deposition likely result from geometric dissimilarity both within and between subjects, and may require more complicated modeling methods than algebraic equations of the kind examined in this study. Copyright © 2017 American Association for Aerosol Research